Digital Banking Balanced Scorecard - Diana Frederica; Yvonne Augustine (Jurnal Keuangan dan Perbankan, 2022)
The study aims to find reliable banking performance indicators by developing the concept of a balanced scorecard. The research employs the method of literature review and measurement quality testing through validity and reliability tests using SmartPLS 3.0. The study found 21 indicators known as Digital Banking Balanced Scorecard. The theoretical implication of this research is that the development of the concept of balanced scorecard has four perspectives and 21 indicators. The contribution of this research is that the banks may take the Digital Banking Balanced Scorecard measurement to assess their performance, especially for those that have implemented banking digitalization. To ensure continuity of bank’s operation, the management needs to perform an analysis on performance required for a strategic decision making. The accurate measurement or reliable indicator for banking performance is, therefore, needed, so that the company management can make decision on the basis of the company's real conditions in the current digitalization era.